PENGARUH MONEY ETHICS DAN RELIGIOSITY TERHADAP TAX EVASION (Studi Pada Wajib Pajak Orang Pribadi Di KPP Pratama Semarang Candisari) - Riska Febriana Ramadani, 12.05.52.0193; Meita Oktaviani, Rachmawati (Students Journal of Accounting and Banking, 2016)
This study was conducted to examine and analyze the influence of money ethics and religiosity against tax evasion. The research method used primary data is by distributing questionnaires to 120 individual taxpayer on KPP Pratama Semarang Candisari. The sampling technique used was convenience sampling. The data analysis techniques used multiple regression analysis using SPSS. The results of the study showed that money ethics influence on tax evasion, howefer religiosity has no effect. Keywords: Money Ethics, Religiosity, Tax Evasion